REPORT ON THE AERIAL PHOTOGRAPHY AND GROUND SURVEYING BY THE SIXTH JAPANESE ANTARCTIC RESEARCH EXPEDITION - Arao YOSHIDA; Seiichi KAKINUMA (National Institute of Polar Research, 1963)
1) Aerial photography Aerial photography started on the 15th of January and finished on the 23rd of January, and nine flights could be done during this time. As the result of these, 987 sheets of vertical photographs by Zeiss Aerotopograph RMK 11, 5/18 camera had been taken, corresponding to 1235 flying kilometers. The average flying altitude was kept 10,000 feet. Totally, including previous expeditions, the photographed area was covered from 37°E to 45°E in longitude along coastal zone continuously. 2) Ground Surveying One astronomical point was newly established in Skallen district, using Wild T2 theodolite for solar observation, on the 11th of January. Its position is as follows : 69°38'15"S. in latitude 39°24'08"E. in longitude 3) Mapping compilation The plotting works, based on vertical photographs, are being carried out in Geographical Survey Institute.